GAMBARAN TINGKAT SOSIAL EKONOMI DAN KEBIASAAN MEROKOK PADA SISWA LAKI-LAKI SMA NEGERI 1 PEKUTATAN, KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA TAHUN 2014 - Agus Satria Jayatama (Intisari Sains Medis, 2016)
SMOKING HABIT AND SOCIAL ECONOMIC LEVEL IN MALE STUDENT OF SMA NEGERI 1 PEKUTATAN, PEKUTATAN DISTRICT JEMBRANA REGENCY IN 2014ABSTRACTBackground: Smoking is one of the health problems in the world are still trying to handle. Smokers usually begins inteenager. The results of the study by the Health Department in 2008 showed that prevalence of smokers in Jembrana was 38.2%. Age of first smoking was highest in the age group 15 to 19 years is 44.1%. The purpose of this study is to describe the smoking habbit of students of SMAN 1 Pekutatan, District Pekutatan, Jembrana Regency in 2014.Â Methodology: This study was a descriptive cross-sectional study. Using a sample of men as many as 75 people who are students of SMAN 1 Pekutatan. Data was obtained using a questionnaire.Results: The results of the study of demographic characteristics, respondents aged 15 to 19 years, started smoking since high school (62.1%). The reason smoking as invited friends (69%), with the average number of cigarettes per day 7.07 rods in suction and filter cigarette smoking entirely. Smoking is the most common time with friends, the most common is the stall hangout with friends. More often get by buying cigarettes, and most parents do not know if they smoke. Respondents who receive a stipend of more than or equal to Rp 10,000, - most do not smoke and who get an allowance of less than Rp 10,000, - entirely non-smoking. Respondents whose parents smoke are also most of the smoke, and the respondents whose parents do not smoke do not smoke too largely.Conclusion: The proportion of smoking male students of SMAN 1 Pekutatan is 38.7%. The results of this study show everyday friends have a high influence on smoking behavior in adolescents. Male students that smoking spend 52,05% of their money to buy cigarettes.